Role of imaging in evaluation of intestinal obstruction - Jaswinder Kaur Mohi; Sunita Kajal; Tejinder Singh; Jasvir Singh; Navkiran Kaur (International Journal of Medical Research and Review, 2017)
Introduction: Small bowel obstruction (SBO) is a common clinical entity that occurs secondary to mechanical or functional obstruction of the small gut, preventing normal passage of its contents. It constitutes 20% of all surgical emergencies for acute abdominal pain and a common cause for hospitalization. Plain abdominal X-ray and ultrasonography were used for initial examination. Now, Computed tomography is the modality of choice for preoperative evaluation of SBO.Aims and Objectives: To evaluate the diagnostic accuracy of various imaging modalities namely plain x-rays of abdomen, ultrasound and computed tomography in the diagnosis of intestinal obstruction with reference to a) The presence or absence of obstruction b) The level of obstructionc) The cause of obstruction.Materials and Methods: It was a hospital based prospective study in which X-Ray and ultrasonography were done as an initial modality for screening and Multi Detector Computed Tomography (MDCT) scan was done later on for detailed evaluation. Relevant history, clinical examination and routine investigations were done.Results: Acute intestinal obstruction: CT scan was found to be superior in predicting a fully correct diagnosis (78%) when compared to ultrasound (29%) which in turn was found to be superior to plain films which provided fully correct diagnosis only in 10% of the cases. Subacute intestinal obstruction- In 62.5 % cases of sub acute intestinal obstruction CT scan provide fully correct diagnosis whereas in none of the cases did ultrasound or plain films provide fully correct diagnosis.Conclusion: CT was found to be superior to ultrasound and plain films in finding out the presence, level as well as cause of obstruction.